1961
DOI: 10.1029/jz066i003p00903
|View full text |Cite
|
Sign up to set email alerts
|

Summary report of strong-motion measurements, underground nuclear detonations

Abstract: Subsurface and surface motion measurements were made on six underground nuclear detonations in the Oak Springs tuff of Nevada Test Site in Operation Hardtack II: Shots Mars (∼13 tons), Tamalpais (∼77 tons), Neptune (∼115 tons), Logan (∼5 kt), Evans (∼30 tons), and Blanca (∼19 kt). Free‐field peak radial acceleration decreased as the inverse third or fourth power of slant range, as for Rainier. Particle velocities attenuated at a rate between the inverse square and inverse cube. Maximum radial and tangential su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1963
1963
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The authors proposed a crustal model consisting of an upper layer 28.5 km thick, an intermediate layer 24.5 km thick, and a Pn velocity of 8.11 km/sec. Adams et al [1961] reported the travel times of P waves from Blanca and Logan to distances as great as 3850 km. They found that their data, out to 900 km, could be fitted by three straight-line travel-time curves.…”
Section: The Underground Nuclear Explosions B Lanca and Logan Which supporting
confidence: 66%
“…The authors proposed a crustal model consisting of an upper layer 28.5 km thick, an intermediate layer 24.5 km thick, and a Pn velocity of 8.11 km/sec. Adams et al [1961] reported the travel times of P waves from Blanca and Logan to distances as great as 3850 km. They found that their data, out to 900 km, could be fitted by three straight-line travel-time curves.…”
Section: The Underground Nuclear Explosions B Lanca and Logan Which supporting
confidence: 66%
“…Adams et al (1961) and Murphy and Lahoud (1969) found that of three types of seismic observables, displacement, velocity, and acceleration, only displacement legitimately follows cube-root scaling. They reason that outside the hydrodynamic region, in the seismic far field, the elastic medium introduces other characteristic lengths and a low-frequency observation such as displacement is less susceptible to these effects.…”
Section: Seismic Data and Methodsmentioning
confidence: 96%
“…A few particular studies are relevant to this study. Adams et al (1961) and Murphy and Lahoud (1969) reported empirical scaling relations for far-field seismic motions (displacement, velocity, and acceleration) versus range. Many studies found different behavior for explosions from different emplacement material strength (e.g., Perret and Bass, 1975) or recording site lithology (e.g., Murphy and Lahoud, 1969).…”
Section: Introductionmentioning
confidence: 97%
“…Seismometers, key diagnostic tools of seismic signatures, measure only displacement. Previous researchers 31,32 have noted that only displacement legitimately follows cube-root scaling analogous to the types presented for air blast effects in Sec. V B. Koper et al 4 have concluded that the peak displacement of the first seismic-signal arrival is the most robust estimator of the yield of the source of all the observables they studied.…”
Section: A Ground-shock Data Analysismentioning
confidence: 70%